Building Students’ Writing Skill by Using Edmodo - Desi Yulastri (Politeknik Negeri Padang, 2015)
Studying a writing subject for fresh year students of English Department in State Polytechnic in Padang is sometimes found very difficult for them. Many students have lack of motivation in this subject. Not only that, lack of grammar and vocabulary is the main barrier for the students in learning writing in English. Using Edmodo, as an online interactive social networking, in writing subject can be an effective way to build students’ writing skill. The positive progress in writing skill begins to appear after integrating Edmodo in writing 1 subject for half of a semester. Most of the students have a better understanding in forming their sentences, indicated in their comments posted in Edmodo. The using of capitalization and punctuation in their sentences has also improved better indicated by their weekly posts in Edmodo. The students also showed a positive attitude toward the writing subject. Their motivation to write and post their comment via Edmodo can be one of the keys for them to improve their writing skill.